Responses of banana plantlets to rhizobacteria inoculation under salt stress condition - Mahmood, Maziah; Abdul Rahman, Zuraida; Mohd Saud, Halimi; Shamsuddin, Zulkifli; Subramaniam, Sreeramanan (American-Eurasian Network for Scientific Information, 2009)
The effects of rhizobacteria inoculation in modified MS medium containing sodium chloride (0.2%) on the biochemical components, physiological characteristics and mineral content of the in vitro banana plantlets were carried out. The presence of rhizobacteria in the medium supplemented with 0.2% sodium chloride resulted in an improvement in growth and root biomass compared to the control (uninoculated). This rhizobacteria inoculation also produced an increase in protein, nitrate, soluble nitrogen and chlorophyll contents of the plantlets cultured in MS modified medium containing 0.2% sodium chloride. The descending order of effectiveness of the rhizobacteria in medium containing 0.2% sodium chloride was: UPMB11>UPMB10>Sp7. The effectiveness of inoculation is increased when associated with boron, nitrogen or carbon into the medium. Thus these bacterial strains could be used as a bioenhancer for growth of in vitro banana plantlets.